The human factor of cybercrime - Leukfeldt, E. R.; Holt, Thomas J. (Routledge studies in crime and society, 2020)
It ain't what it is, its the way that they do it? Why we still don't understand cybercrime / Mike McGuire -- Contributions of criminological theory to the understanding of cybercrime offending and victimization / Adam Bossler -- The open and dark web : facilitating cybercrime and technology-enabled offenses / Claudia Flamand and David Décary-Hétu -- Predictors of cybercrime victimization : causal effects or biased associations? / Steve van de Weijer -- Virtual danger : an overview of interpersonal cybercrimes / Jordana Navarro -- Sexual violence in digital society : understanding the human and technosocial factors / Anastasia Powell, Asher Flynn and Nicola Henry -- Cybercrime subcultures : Contextualizing offenders and the nature of the offense / Thomas J. Holt -- On social engineering / Kevin Steinmetz, Richard Goe and Alexandra Pimentel -- Contrasting cyber-dependent and traditional offenders : a comparison on criminological explanations and potential prevention methods / Marleen Weulen Kranenbarg -- Financial cybercrimes and situational crime prevention / Rutger Leukfeldt and Jurjen Jansen -- Modelling cybercrime development : the case of Vietnam / Jonathan Lusthaus -- Humanising the cybercriminal : markets, forums and the carding subculture / Craig Webber and Michael Yip -- The roles of 'old' and 'new' media tools and technologies in the facilitation of violent extremism and terrorism / Ryan Scrivens and Maura Conway -- Child sex abuse images and exploitation materials / Roderic Broadhurst -- Policing cybercrime : responding to the growing problem and considering future solutions / Cassandra Dodge and George Burruss -- Responding to individual fraud : Perspectives of the 'Fraud Justice Network' / Cassandra Cross -- The ecology of cybercrime / Benoît Dupont -- Displacing big data : how criminals cheat the system / Alice Hutchings, Sergio Pastrana and Richard Clayton.